Model Dinamis Analisis Keputusan Penanganan Penyebaran Covid-19 Menggunakan Causal Loop Diagram - Muhammad Safii; Husain Husain; Mochamad Wahyudi; Muhammad Zarlis (Jurnal Informatika, 2021)
The spread of Corona Virus or Covid 19 is very fast and has become a pandemic for all countries in this world. In a very dynamic and complex development process consisting of many interrelated and diverse components, each of which has different goals. Regarding the dynamic and complex challenges in the field of developing corona virus spread, the ability to identify is needed to reduce the circulation of the virus. For this reason, it is necessary to look further into the factors that influence and inhibit the spread of the virus and what strategies are needed and analyze the dynamically dynamic causes of these factors using the method of approach that uses the Cause Circle Diagram (CLD) system. ). The purpose of this research is to get the right solution in making decisions to handle the spread of corona virus through a system approach with a Causal Loop Diagram (CLD) model.